Effect of signal molecules for enhanced production of boeravinone B in shoot cultures of Boerhaavia diffusa (L.) - Sharma, Savita; Sharma, Jyotsna; Singh, Deepika; Sharma, Vandana; Mallubhotla, Sharada (Emirates Journal of Food and Agriculture, 2022)
High performance thin layer chromatography (HPTLC) analysis was used to analyze boeravinone B production in shoot cultures of Boerhaavia diffusa under the influence of different biotic [yeast extract (YE), cellulase (CL)] and abiotic [salicylic acid (SA), jasmonic acid (JA)] signal molecules at different concentrations. Biomass accumulation and boeravinone B production in shoot cultures raised on agar solidified medium were analysed for a period of 30 days to optimize the suitable age of culture for treatment with signal molecules. A maximum yield of boeravinone B (5.74 %) was obtained after 7 days and therefore treatments were performed at a gap of 3, 6 and 9 days. Signal molecules used at varied concentrations differentially influenced the shoot cultures for biomass regeneration and culture growth. Cellulase treatment (0.5 mgl-1) resulted in maximizing biomass (1.30gm) and boeravinone B content (22.7 %) after 6 days of exposure time as compared to other treatments used in the study. Thus the current study can be exploited further for enhancement of boeravinone B from shoot cultures of Boerhaavia diffusa.